Analisis Proksimat dan Organoleptik Penggunaan Ikan Malaja sebagai Pembuatan Kerupuk Kemplang - Abdul Razak Thaha; Zainal Zainal; Sitti Khadijah Hamid; Denny Saputra Ramadhan; Nasrul Nasrul (Media Kesehatan Masyarakat Indonesia, 2018)
Malaja fish only consumed by adults so it is necessary to make children can consume them in the societyof palopo. Crackers are snacks that can be eaten anytime so that if used as fish crackers that contain useful nutrients.This study aims to determine the organoleptic and proximate test of malaja fish crackers. This research wasdesigned using experimental method with Completely Single Randomized Design with 5 treatments and 3 replicationsto 15 experimental units. The results showed that the water content of kempuk kemplang was from 1.50-5.12%. The highest water content was obtained in the control treatment. The highest protein content is producedfrom A4 treatment. The highest percentage of ash content was found in A4 treatment and lowest in treatment A1.The test results showed that the highest aroma score obtained at treatment A1 ie 3.27. The highest Color Scorevalue is obtained from treatment A0 (control). The highest value of taste scores was obtained in the treatment of A2and A3. The addition of maladies of 15% and 25% is favored by panelists. It was concluded that the highest contentin the proximate test was based on the treatment group ie carbohydrate in the treatment, fat in the treatment, proteinat treatment A4. Organoleptic test with the best treatment on cracker production of malaja fish is A2 treatment.